Analysis of Mitigation Performance Budget in Transportation Sector in Yogyakarta Province - Joko Tri Haryanto (Research and Development Agency Ministry of Home Affairs, 2017)
Yogyakarta province is one of the regions with growing concerns towards increasing carbon emission from growing private transportation usage. In response, the provincial government enacted Local Mitigation Plan by the Governor Regulation Number 51 Year 2012, in accordance with the Presidential Decree No. 61 Year 2011 on National Mitigation Plan for Reducing Glass House Gas (GHG) Emission. The plan places energy and transport sector as top priority programs that should be controlled and regulated by the local government. This paper examines the implementation of the plan by looking at the derivation of the local mitigation planning into government budgeting. It employs project sustainability analysis to elaborate the presence of factors affecting the application of the plan into government programs. The study reveals that in general, the government programs reported in the strategic and performance indicators on Government Performance Report (LAKIP) in transportation sector are in accordance with the local mitigation plan. Almost 80% from 25 core activities in the Local Mitigation Plan, can be described in each of the strategic objectives and performance indicators LAKIP. Only five core activities can not be translated into strategic objectives and performance indicators on LAKIP. Meanwhile, for supporting documents, approximately 52% has occurred compatibility between Local Mitigation Plan document with strategic goals and performance indicators in LAKIP. However, it is necessary for the government to make adjustments in a number of activities to improve the quality of planning as well as optimize the effectiveness of the budget.